Biostratigraphic Zonation and Depositional Environments of the BB Well, Niger Delta Basin: A Foraminiferal Perspective (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study addresses persistent stratigraphic uncertainties in the hydrocarbon-rich Niger Delta by integrating foraminiferal biostratigraphy with high-resolution sedimentology. Foraminifera were extracted from forty-one ditch cuttings retrieved from BB Well in the Niger Delta Basin using standardized disaggregation, sieving and picking techniques. This biostratigraphic data was synthesized with lithological descriptions and gamma-ray wireline logs to construct a composite graphic log, enabling the correlation of biofacies with distinct lithofacies. Results delineate two key intervals within the Agbada Formation: an upper section (Lithofacies A: 2100–2500 m) of alternating sands and shales deposited in barrier bar complexes, and a lower section (Lithofacies B: 2500–3100 m) of thick shales with minor channel and turbidite sands. Paleoenvironmental analysis based on benthic foraminiferal assemblages reveals a major transgressive-regressive cycle. The succession records a Middle Miocene shift from inner neritic to bathyal conditions, marked by a maximum flooding surface, followed by a Late Miocene shallowing-upward trend to inner/middle neritic settings. Biozonation confirms a Middle to Late Miocene age for the studied section. Globigerinoides immaturus – Globorotalia siakensis and Globorotalia tumida – Globigerinoides margaritae Assemblage Biozones which correlate with N14-N15 and N16 – N17 planktic foraminifera biozone of Berggren et al. (1998) were established for the studied section. This integrated multi-proxy approach establishes a robust chronostratigraphic framework and directly links depositional processes to sea-level changes. The resulting model clarifies the basin's stratigraphic evolution and provides an enhanced template for predicting reservoir distribution and architecture, with direct applications for exploration in the Niger Delta and similar deltaic systems.